The Effect of Ginger Aromatherapy Inhalation on Emesis Gravidarum in 1st Trimester Pregnant Womenat PMB Maghpiro - Apriyani, Titin; Rahmadayanti, Ade Marlisa; Putri, Sartika Dwi Yolanda (Indonesian Journal of Global Health Research, 2024)
Emesis gravidarum is a common complaint presented by young pregnancies. Pregnancy causes hormonal changes in women because there is an increase in the hormones estrogen, progesterone and the hormone gonodotropin released by the placenta. These changes in hormones cause symptoms of dizziness and nausea and vomiting, especially in the first trimester of pregnancy. One of the aromatherapy that is often used is ginger, ginger aromatherapy is also effective in reducing emesis gravidarum in pregnant women in the first trimester of pregnancy and reducing nausea and vomiting in multigravida women. The content of essential oils in ginger which has a relaxing effect, gingerol and oleoresin which give a warming effect so that nausea and vomiting can decrease. The effect of ginger on the central nervous system was shown in animal experiments with gingerol, which resulted in a decrease in the frequency of vomiting. This study aims to determine whether there is an effect of ginger aromatherapy inhalation on emesis gravidarum in first trimester mothers at BPM Maghpiro. The design of this research is quasi experiment which is one group preposttest. The data analysis used is Bivariate analysis. Research time from April to July. The population in this study was first trimester pregnant women, totaling 15 respondents. Data collection was carried out using the PUQE-24 Questionnaire. The results of the study used the t-test technique which showed that before being given ginger aromatherapy, 10 respondents (66.7%) experienced moderate nausea and vomiting and 5 respondents (33.3%) experienced severe nausea and vomiting. After being given ginger aromatherapy inhalation, 15 respondents (100%) experienced mild nausea and vomiting. The average value before and after giving ginger aromatherapy inhalation to nausea and vomiting in pregnant women, where from 15 respondents obtained results before ginger aromatherapy inhalation was carried out with a mean value of 12.07 and after ginger aromatherapy inhalation obtained a mean value of 4.33, which This means there is an effect before and after giving ginger aromatherapy inhalation. Based on this, there is a decrease in the frequency of nausea and vomiting in pregnant women in the 1st trimester after being given ginger aromatherapy inhalation.